(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Imaging is fundamental to the diagnosis of congenital heart disease and is required at all stages of case care. Cardiac magnetic resonance imaging (CMRI) provides high-resolution, isotropic, three-dimensional data. The aim of this work was to assess role of CMRI in post-surgery evaluation of pediatric surgically corrected CHD. Methods: This prospective research was carried out on 33 cases from 5 to 21 years old, referred postoperatively to be examined by CMRI examination. All cases were subjected to Echo and CMRI examination. Results: The most frequent CHD coming for post-surgery evaluation was TOF which represented 42% of the cases. The common post-surgery complication in all interventions of TOF repair was PR found in 71% of cases after TAP while 14% on top of homograft PA conduit. Combined PA stenosis and PR found in 29% on top of TAP while 7% on top of homograft PA conduit. RV dysfunction found in (28.5%) on top of RV dilatation. The cases of single ventricle repair (27% of cases) with the common complication functional ventricular dysfunction in 44%. After TGA repair (15%), the common complications were PA branch stenosis (20%), PA valve stenosis (20%), LV dysfunction (40%). Conclusions: CMRI provides a powerful non-invasive imaging tool, giving anatomic and haemodynamic information that echo and catheterization alone don’t provide, during post-surgical follow up of CHD.